FILSAFAT KEAGAMAAN ISLAM DI ANDALUSIA - Nazilatul Laili Sa’adah; Rusma Yulidawati (Tarbawi, 2022)
This manuscript delves into philosophical research that examines philosophy in the context of Islam as a religion, where philosophy is categorized as a discipline that demands deep reflection on tangible objects. The concept of "human" begins with a basic understanding, namely the intrinsic difference between humans and divine nature regarding beliefs. Just as religion cannot be entirely explained by science, knowledge derived from human reason, separate from cultural traditions and sacred teachings, is also limited. Philosophy often confronts problems that are beyond the reach of science. Philosophy, when it intersects with faith and religious traditions, becomes relevant and harmonious when believers take the initiative to understand and respect their own religious teachings, doctrines, and beliefs logically. As a result, philosophy is no longer seen as the adversary of religion. The author of this manuscript presents a new perspective on religion as a special entity that also encompasses substantial elements, with the hope of fostering a broader understanding and inter-religious interaction and providing a clear conceptual framework within the discipline of philosophy.